Hovenia dulcis T. extract and Glycyrrhiza glabra as natural antioxidants in Bologna mortadella - Darlene Cavalheiro; Gisiéli Carla Morandin; Sabrina Vicentini Schaefer; Adrieli Maiandra Piccinin do Amaral; Luana Bettanin; Georgia Ane Raquel Sehn (Revista Principia)
Pseudo-fruits of Hovenia dulcis T. are sweet-tasting, edible, and contain numerous nutrients and a significant amount of phenolic compounds, which could serve as a source of natural antioxidants. In this context, this study aimed to evaluate the addition of H. dulcis T. extract and licorice root extract (licrezzTM) in the formulation of Bologna-type mortadella and to investigate the inhibition of lipid oxidation during cold storage, to assess their antioxidant properties. Mortadella samples were prepared in duplicate with sodium erythorbate (control), licrezzTM (commercial extract from Glycyrrhiza glabra), and H. dulcis extract, at a concentration of 0,1%. The samples were evaluated for proximate composition, microbiological characteristics, texture profile, lipid oxidation, nitrite content, instrumental color, pH, and water activity. Mortadella with H. dulcis extract did not show significant differences from the control in terms of proximate composition, microbiological characteristics, or texture profile. However, they exhibited slightly lower, but comparable results in the Thiobarbituric Acid Reactive Substances (TBARS) assay during the 28 days of refrigerated storage. The control and H. dulcis extract samples showed approximately a ninefold increase in TBARS values by the end of storage, while licrezzTM showed a twenty-sixfold increase. On the other hand, H. dulcis extract exhibited similar behavior to licrezzTM regarding residual nitrite content. Thus, H. dulcis pseudo-fruits extract shows potential for use as a natural antioxidant in emulsified meat products, alone or in combination with Glycyrrhiza glabra.